Faktor prioritas pemilihan lokasi perumahan berdasarkan preferensi penghuni pada kawasan peri urban di Kecamatan Jaten, Kabupaten Karanganyar - Melinda Setyoningrum; Chrisna Trie Hadi Permana; Hakimatul Mukaromah (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Rapid urbanization in urban areas has increased housing demand and accelerated residential development in peri-urban regions. Jaten Sub-district, Karanganyar Regency, has functioned as a peri-urban area of Surakarta City since 1990 and has experienced significant housing growth, land-use change, and rising population density. This condition requires an understanding of community preferences in housing location selection to support sustainable regional development. This study aims to identify priority factors influencing community decision-making in selecting housing locations in the peri-urban area of Jaten Sub-district. A deductive quantitative approach was employed, supported by factor analysis. Data were collected through surveys of housing residents, with initial variables including accessibility, environment, ownership attractiveness, facilities, and infrastructure. Factor analysis was conducted using SPSS to generate new factor components based on loading values. The results indicate that the most influential factors in peri-urban housing location selection are ease of access to the city center, disaster-free environmental conditions, certainty of land ownership, availability of commercial facilities, and the quality of drainage and solid waste networks. These findings emphasize the importance of integrating accessibility, regional safety, and basic infrastructure in peri-urban housing development planning.